Value-Based Total Performance Excellence Model: A Conceptual Framework for Organisations - Mokhtar, Abdullah; M. R., Abdul Hamid; Zainol, Mustafa; Nooreha, Husain; Fazli, Idris; Nur Riza, Mohd Suradi; Wan Rosmanira, Ismail (Taylor & Francis, 2012)
This article presents a conceptual framework for the development of a value-based total performance excellence model (VBTPEM) in organisations. This model signifies core values as a strategic component for an organisation to achieve total performance excellence. The VBTPEM is an extension of the earlier version of the TPEM proposed by Husain et al. [Husain, N., Abdullah, M., Idris, F., & Sagir, R.M. (2001). The Malaysian total performance excellence model: A conceptual framework. Total Quality Management, 12(7&8), 926 –931] and Abdullah et al. [Abdullah, M., Husain, N., & Nik Hassan, N.M. (2008). Guidelines for implementing value-based total performance excellence model in business organizations. Presentations at the The Islamic Perspective Forum, Manila,Philippines. This extension integrates the intangible parts of performance measurement that have become a pivotal issue in many organisations. Hence, this paper discussed the core values associated with each of the criteria in the TPEM framework. The significance of the study is that it contributes to the extended version of performance measurement research by integrating core values into the total performance excellence framework. The notion of values-driven total performance excellence applies to an organisation that achieves superiority in both financial and non-financial performances due to reinforcement and internalisation of balanced, viable, aligned, and authentic core values in that organisation [Hultman, K., & Gellerman, B. (2002). Balancing individual and organisational values: Walking the tightrope to success. Hoboken, NJ: John Wiley & Sons].